Carbohydrate supplementation delays DNA damage in elite runners during intensive microcycle training - Vieira de Sousa, M.; Madsen, K.; Fukui, R.; Santos, A.; Rossi da Silva, M. E. (European Journal of Applied Physiology, 2012)
The aim of this study was to evaluate the effect of carbohydrate supplementation on free plasma DNA and conventional markers of training and tissue damage in long-distance runners undergoing an overload training program. Twenty-four male runners were randomly assigned to two groups (CHO group and control group). The participants were submitted to an overload training program (days 1-8), followed by a high-intensity intermittent running protocol (10 × 800 m) on day 9. The runners received maltodextrin solution (CHO group) or zero energy placebo solution as the control equivalent before, during, and after this protocol. After 8 days of intensive training, baseline LDH levels remained constant in the CHO group (before: 449.1 ± 18.2, after: 474.3 ± 22.8 U/L) and increased in the control group (from 413.5 ± 23.0 to 501.8 ± 24.1 U/L, p < 0.05). On day 9, LDH concentrations were lower in the CHO group (509.2 ± 23.1 U/L) than in the control group (643.3 ± 32.9 U/L, p < 0.01) post-intermittent running. Carbohydrate ingestion attenuated the increase of free plasma DNA post-intermittent running (48,240.3 ± 5,431.8 alleles/mL) when compared to the control group (73,751.8 ± 11,546.6 alleles/mL, p < 0.01). Leukocyte counts were lower in the CHO group than in the control group post-intermittent running (9.1 ± 0.1 vs. 12.2 ± 0.7 cells/µL; p < 0.01) and at 80 min of recovery (10.6 ± 0.1 vs. 13.9 ± 1.1 cells/µL; p < 0.01). Cortisol levels were positively correlated with free plasma DNA, leukocytes, and LDH (all r > 0.4 and p < 0.001). The results showed that ingestion of a carbohydrate beverage resulted in less DNA damage and attenuated the acute post-exercise inflammation response, providing better recovery during intense training.